Integrated energy system - Hong, Go Yau; Lazaro, Marie Joy; Lim, Nelson N. (College of Engineering, 1977)
Raw materials: 7.2 tons Urea, 4763 tons of Pig Manure, 539 tons of Chicken Manure -- Products: Electricity - 14542 KW-hr, Gas (bio-gas) - 292000 m3, Fertilizer - 2372 tons, Chlorella - 72000 kg -- Total capital investment: Php 1,365,629 -- Production cost: Php 303,098 -- Profit: Php 204,252 -- Rate of Return of Capital: 14.95% -- Payout Period: 5.28 years